The Efficiency and Public Transport Accessibility of Indirect State Administration in the Czech Republic - Iveta Vrabková; Ivana Vaňková; Igor Ivan (Review of Economic Perspectives, 2016)
This paper examines the efficiency and public transport accessibility of indirect (devolved) state administration performed by municipalities with extended powers (hereinafter MEPs) in the Czech Republic. Our aim is to evaluate the efficiency of the revenues made by municipalities with extended powers, through performing powers delegated to them by the state administration, and those municipalities' public transport accessibility as of 31 December, 2014. The rate of efficiency is tested on an output-oriented Free Disposable Hull model. One input variable is selected - the operating expenses of the municipal offices recalculated per inhabitant of the municipality's administrative district - and two output variables are selected: contribution to the performance of state administration, recalculated per inhabitant of the municipality's administrative district, and revenues from administrative fees per inhabitant of the municipality's administrative district. The municipality's offices' transport accessibility is evaluated via network analysis using ArcGIS software. The article investigates the hypothesis that public administration deconcentration practices logically result in higher security costs and therefore inefficiency. The results reveal that only 66 of the country's 205 MEPs are efficient and that operating expenses and state contributions for the performance of state administrative tasks play a significant role in these results. Efficiency is less significantly influenced by administrative fee revenues. Public transport accessibility is analyzed for two time intervals - 6:00 to 8:00 am and 1:00 to 2:00 pm - on Tuesdays. The degree of accessibility is defined using a six-point scale of accessibility. The results show that the best accessibility is in the morning hours, when the offices are accessible for 68.8% of the population aged 15+ in the Czech Republic; the worst accessibility is in the afternoon hours when only 2% of the population aged 15+ can access the offices.
Keywords: 330